Flue gas control parameter effects of biomass carbonization with heating coil on the production of lotus charcoal for odor absorption - Chunkaew, Phairoach; Khadwilard, Aphirak; Tevata, Anurat; Thawonngamyingsakul, Chakkraphan; Kosalanun, Sumroum (Frontiers in Engineering Innovation Research, 2024)
This research aimed to study the effects of flue gas control parameters including flue gas temperature and flue gas velocity of biomass carbonization with heating coil on the production of lotus charcoal for odor adsorption. The odor absorbing charcoal machine had a drying chamber of 50 × 45 × 35 cm3 which could contain 6 pods. Hot smoke was generated from a 100 liter kiln. Next, the hot smoke was increased temperature by using a heater before entering the drying chamber. At the kiln, a fan was installed for blowing the air to the kiln. The fan could control the speed for adjusting the air to the kiln. Experiment, the lotus had an initial moisture content of 86.19±1.67 % wet basis and was dried to the final moisture content of 0 % wet basis. The control variables were smoke temperatures of 200, 250 and 300°C and smoke velocities of 1.22, 1.74 and 2.27 m/s. It was found that at flue gas temperatures of 200, 250 and 300˚C, the production time for odor absorber was 120, 100 and 60 min, respectively, but at constant flue gas temperature and increasing flue gas velocity, the production time for odor absorber was the same because the raw materials did not come into direct contact with the flue gas. The raw materials were packed in another layer of the raw material cabinet to prevent the lotus from burning and turning into ash so the exhaust gas touched the outer wall surface of the raw material cabinet. Therefore, the drying method was a heat radiation drying method and the drying result was to depend on only one temperature variable. An iodine adsorption and a specific energy consumption were studied. It was found that increasing the temperatures and the velocities of hot smoke, the iodine adsorption and the specific energy consumption were increased. At 300˚C with the flue gas velocity 2.27 m/s had the maximum iodine adsorption value of 1176.32±21.562 mg/g.